Aldehyde and Ketone Synthesis by P450-Catalyzed Oxidative Deamination of Alkyl Azides - Giovani, Simone (ChemCatChem, 2016)
Heme-containing proteins have recently attracted increasing attention for their ability to promote synthetically valuable transformations not found in nature. Following the recent discovery that engineered variants of myoglobin can catalyze the direct conversion of organic azides to aldehydes, we investigated the azide oxidative deamination reactivity of a variety of hemoproteins featuring different heme coordination environments. Our studies show that although several heme-containing enzymes possess basal activity in this reaction, an engineered variant of the bacterial cytochrome P450 CYP102A1 constitutes a particularly efficient biocatalyst for promoting this transformation, exhibiting a broad substrate scope along with high catalytic activity (up to 11,300 TON), excellent chemoselectivity, and enhanced reactivity toward secondary alkyl azides to yield ketones. Mechanistic studies and Michaelis-Menten analyses provided insights into the mechanism of the reaction and the impact of active site mutations on the catalytic properties of the P450. Altogether, these studies demonstrate that engineered P450 variants represent promising biocatalysts for the synthesis of aryl aldehydes and ketones via the oxidative deamination of alkyl azides under mild reaction conditions.